The role of emotional intelligence on the outcome of negotiation in construction procurement - Wai Khwan, Lee (2014)
Negotiation is a process that involves the interaction of emotion. In the other word, Emotion has significant impact in manipulate the result of negotiation. Both of these elements are relevant to each other indirectly. The interesting facts inspire the thought to create this research. This research was conducted to recognize the effect of the dimensions of Emotional Intelligence (EI) on the outcome of negotiation in construction procurement. There are two main objectives in this study, to identify the dimension of EI that affects the outcome of negotiation in construction procurement conflict and to determine the component of EI that has the greatest influential to the outcome of negotiation in construction procurement conflict. Sets of questionnaires were distributed and data was collected by mail and walk-in. Based on feedbacks from the respondents, most of them are aware about the importance of EI in negotiation. The result from the analysis shown that, the four dimensions of EI is identified as factor which can affects the outcome of negotiation in construction procurement conflict. Lastly, the result of comparison of average mean between all dimensions shown relationship management is the main factors which influencing the outcome of negotiation in construction procurement conflict